The Making of The Australian National University 1946-1996 - Foster, Stephen (ANU Press, 2009)
The Australian National University has always been a university with a difference. Conceived in the mid-1940s to serve Australia's post-war needs for advanced research and postgraduate training, it quickly embraced the ideals and traditions of Oxford and Cambridge. Undergraduate teaching was introduced in 1960, following amalgamation with Canberra University College. The University continued to adapt to changes in Australian society, while retaining much of its unique structure and objectives. Stephen Foster and Margaret Varghese trace the history of ANU from its wartime origins to its fiftieth anniversary in 1996, featuring many of the prominent Australians who contributed to its making: 'Nugget' Coombs, Howard Florey, Mark Oliphant, W.K. Hancock, Douglas Copland, John Crawford, Peter Karmel; and others who stood out in particular fields, such as J.C.Eccles, Arthur Birch, Manning Clark, Russell Mathews, Ernest Titterton, Beryl Rawson, John Mulvaney, John Passmore and Frank Fenner. The Making of The Australian National University explores many themes in higher education during the last half century, including academic freedom, relations between universities and politicians, recruitment practices, the 'two cultures' of science and the humanities, collegial versus managerial structures, equality of opportunity, student politics, academics and architecture and universities in the marketplace. This is an affectionate and critical account of a remarkable Australian institution; and, more broadly, a fascinating study of how institutions work.